Pharmacological blockade of the fatty acid amide hydrolase (FAAH) alters neural proliferation, apoptosis and gliosis in the rat hippocampus, hypothalamus and striatum in a negative energy context - Rivera, Patricia; Bindila, Laura; Pastor, Antoni; Pérez-Martín, Margarita; Pavón, Francisco J.; Serrano, Antonia; de la Torre, Rafael; Lutz, Beat; Rodríguez de Fonseca, Fernando; Suárez, Juan (Frontiers in Cellular Neuroscience, 2015)
Endocannabinoids participate in the control of neurogenesis, neural cell death and gliosis. The pharmacological effect of the fatty acid amide hydrolase (FAAH) inhibitor URB597, which limits the endocannabinoid degradation, was investigated in the present study. Cell proliferation (phospho-H3+ or BrdU+ cells) of the main adult neurogenic zones as well as apoptosis (cleaved caspase-3+), astroglia (GFAP+), and microglia (Iba1+ cells) were analyzed in the hippocampus, hypothalamus and striatum of rats intraperitoneally treated with URB597 (0.3 mg/kg/day) at one dose/4-days resting or 5 doses (1 dose/day). Repeated URB597 treatment increased the plasma levels of the endocannabinoids oleoylethanolamide, palmitoylethanolamide and arachidonoylethanolamine, reduced the plasma levels of glucose, triglycerides and cholesterol, and induced a transitory body weight decrease. The hippocampi of repeated URB597-treated rats showed a reduced number of phospho-H3+ and BrdU+ subgranular cells as well as GFAP+, Iba1+ and cleaved caspase-3+ cells, which was accompanied with decreased hippocampal expressions of cannabinoid CB1 receptor and FAAH. In the hypothalami of these rats, the number of phospho-H3+, GFAP+ and 3-weeks-old BrdU+ cells was specifically decreased. The reduced striatal expression of CB1 receptor in repeated URB597-treated rats was only associated with a reduced apoptosis. In contrast, the striatum of acute URB597-treated rats showed an increased number of subventricular proliferative, astroglial and apoptotic cells, which was accompanied with increased Faah expression. Main results indicated that FAAH inhibitor URB597 decreased neural proliferation, glia and apoptosis in a brain region-dependent manner, which were coupled to local changes in FAAH and/or CB1 receptor expressions and a negative energy context.